Ruthenium(II) Complex Based Photodiode for Organic Electronic Applications - Tataroglu, A.; Ocaya, R.; Dere, A.; Dayan, O.; Serbetci, Z.; Al-Sehemi, Abdullah G.; Yakuphanoğlu, Fahrettin (Springer, 2018)
In this study, the electrical and photoresponse properties of a photovoltaic device with Ruthenium(II) complex interfacial thin film were investigated. Heteroleptic Ru(II) complex including bidentate and tridentate ligands thin film was coated on n-Si substrate by the spin coating technique. From current-voltage (I-V) measurements of an Au/Ru(II)/n-Si photodiode, it is observed that the reverse bias current under light is higher than that of the current in the dark. This indicates that the photodiode exhibits a photoconducting characteristic. The transient measurements such as photocurrent, photocapacitance and photoconductance were performed under various illumination conditions. These measurements indicate that the photodiode has a high photoresponsivity. The electrical parameters such as barrier height (I broken vertical bar(b)), ideality factor (n) and series resistance (R (s)) of the photodiode were determined from the analysis of I-V characteristics. Moreover, the capacitance/conductance-voltage characteristics of the photodiode highly depend on both voltage and frequency. Results show that the heterojunction can be used for various optoelectronic applications.
Keywords: Transition-metal complex; ruthenium/Ru(II); illumination effects